Interpersonal, intertemporal and spatial variation in risk perceptions: evidence from East Africa - Doss, C.; McPeak, J.G.; Barrett, Christopher B. (Elsevier, 2008)
This study investigates variation over time, space and household and individual characteristics in how people perceive different risks. Using original data from the arid and semi-arid lands of East Africa, we explore how individuals assess their relative level of concern about risks. The primary determinants of risk rankings are found to be changing community level variables over time, with household specific and individual specific variables exhibiting much less influence. Individuals throughout this area are most concerned about food security and human health, so that development efforts that directly address these problems should be given the highest priority.